Analisis Praktik Pendidikan Kesehatan Reproduksi Remaja Oleh Guru Bimbingan dan Konseling pada SMP yang Berbasis Agama di Kota Semarang - Zaenal Sugiyanto; Suharyo Suharyo (JURNAL DIAN, 2011)
One of fhe causes of reproduction health problem of junior high school sfudents is the lack of correct information about KRR forteenagers. KRR education practice can be influenced by cultural factor like religious norm. This research is aimed to describe the education practice of teenagerls reproduction health done by students counselor (BK) of religion based junior high school ini Semarang and to explain what factors play roles in such practice. This research is conducted by using qualitative method. The data were gathered through in-depth interview. The data were analyzed by using content analysis. The result shows that training of KRR education for counselors of religion based junior high schools is not widely spread and it is lack of frequency. All informants have conducted KRR education but it is not implemented well. The material, method, frequency, and the counselor's role in KRR education are not yet sufficient. Their perception and attitude are good, and they accept positively and suppori KRR education for junior high school students. Not all religion based junior high schools have KRR education facilities such as books, CDs, magazines, and visual aid about KRR. Most principals of religion based junior high schools have done effortsthat support KRR education program but it is not optimal. If is suggested that related office such as health and education office, BKKBN coordinate to improve the counselors' skill in KRR,provide the appropriafe KRR learning tools for religion based junior high schools, and advocate school principals.Keywords: councelors, KRR education, religion based junior high schools